Immune reconstitution and severity of COVID‐19 among hematopoietic cell transplant recipients. Issue 4 (3rd April 2021) - Malek, Alexandre E.; Adachi, Javier A.; Mulanovich, Victor E.; Sassine, Joseph; Raad, Issam I.; McConn, Kelly; Seiler, Garret T.; Dhal, Udit; Khawaja, Fareed; Chemaly, Roy F.
Abstract: Severe acute respiratory syndrome coronavirus 2 can lead to life‐threatening coronavirus disease 2019 (COVID‐19) infections in patients with hematologic malignancies, particularly among hematopoietic cell transplant (HCT) recipients. We describe two patients with COVID‐19 during the pre‐engraftment period after HCT and review previous reports of COVID‐19 in HCT recipients. Because of significant mortality from COVID‐19, primarily after allogeneic HCT, early, preemptive, and optimal directed therapy may improve outcomes and reduce the mortality rate but still needs to be established in clinical trials.